2022
DOI: 10.3390/su142416573
|View full text |Cite
|
Sign up to set email alerts
|

One Step Back or One Step Forward? Effects of Grade Retention and School Retention Composition on Portuguese Students’ Psychosocial Outcomes Using PISA 2018 Data

Abstract: Grade retention is a common practice applied to academically struggling students within the Portuguese context. Studies investigating the psychological experiences of grade-retained students are still scarce. In addition, most studies tend to neglect the multilevel nature of the school context. This study examines the effects of grade retention in grades 1–9 on Portuguese students’ psychosocial outcomes by the age of 15, using PISA 2018 data. Using a quasi-experimental design through full matching, we reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Additionally, we were unable to examine the effects of the school context, specifically, the proportion of repeaters in the school, on the relationship between grade retention and psychosocial outcomes. Previous studies have demonstrated that the composition of retained students in a school also impacts students' psychosocial outcomes (Demanet & Van Houtte, 2016; Hong & Yu, 2008; Pipa & Peixoto, 2022; Van Canegem et al, 2021). Hence, we recommend that future studies consider this moderating variable when assessing the effects of grade retention.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Additionally, we were unable to examine the effects of the school context, specifically, the proportion of repeaters in the school, on the relationship between grade retention and psychosocial outcomes. Previous studies have demonstrated that the composition of retained students in a school also impacts students' psychosocial outcomes (Demanet & Van Houtte, 2016; Hong & Yu, 2008; Pipa & Peixoto, 2022; Van Canegem et al, 2021). Hence, we recommend that future studies consider this moderating variable when assessing the effects of grade retention.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%